Cell adhesion in development: a complex signaling network. - Thiery, J.P. (Current Opinion in Genetics and Development, 2003)
Cell-adhesion molecules play a major role in morphogenesis and organogenesis. In vertebrates, a significant fraction of genes encode cell-adhesion molecules. Multiple signal-transduction pathways have been described that modulate the adhesion process. These pathways have been studied in great detail for cadherins and integrins - two major adhesion systems controlling cell-cell and cell-substrate interactions. Recent findings confirm that a given cell-adhesion molecule can be implicated at different stages of development in processes as diverse as cell positioning, tissue patterning and compartmentalization, axon guidance and synaptogenesis. Clearly, a wide variety of new biophysical techniques and genomic approaches will permit analysis of the roles of adhesive interactions in development to be addressed with far greater precision.